EXPLORING PEER COUNSELORS’ MULTICULTURAL UNDERSTANDING: ASSESSING THE URGENCY OF MULTICULTURAL COUNSELING IN ISLAMIC UNIVERSITIES - Ermalianti, Ermalianti; Rahmi, Nurul; Istati, Mufida (LP2M IAI Al-Khairat Pamekasan, 2024)
Effective peer counseling needs to have good cultural competence to ensure effective communication with the counselee. Cultural competence is increasingly important in higher education institutions as campuses are places where students from diverse backgrounds gather. Unfortunately, research exploring the perspectives of peer counselors in Islamic universities still needs further exploration. This study aims to bridge this gap by exploring the perspectives of prospective peer counselors regarding their multicultural understanding. Using a cross-sectional survey design, this research explores the perspectives of thirty-four prospective peer counselors in an Islamic university in Banjarmasin, South Kalimantan. The instrument used is a cultural awareness questionnaire developed based on multicultural awareness theory and cognitive stage development theory. The results indicate that the level of multicultural awareness among Islamic university students still needs improvement, as participants expressed agreement with 82% of items related to duality, indicating that they have a limited view of other cultures and their perspectives on other cultures are still influenced by the perspectives of others. This study then offers several implications to enhance their multicultural awareness to prepare them to become competent peer counselors.